ANALISIS PENDAPATAN DAN RISIKO USAHATANI JAGUNG DI KECAMATAN METRO KIBANG KABUPATEN LAMPUNG TIMUR - Woeniar Michelle Keny; Fembriarti Erry Prasmatiwi; Dwi Haryono (Lampung University, 2022)
This study aims to examine the comparison of income, risk, risk mapping, and risk management strategies by farmersof corn farming in dry land and rainfed land. The survey was conducted in Metro Kibang District, East Lampung Regency in January 2021. The respondents were randomly selected as many as 70 farmers consisting of 40 dry land farmers in Margototo Village and 30 rainfed land farmers in Kibang Village. The data were analyzed using the income difference test, the coefficient of variation difference test, risk mapping, and descriptive analysis of farmers’ strategies. The results showed that the income of corn farming grown in dry land and in rainfed land was different, but both were profitable. The risk of production and income of corn farming in dry land is greater than in rainfed land. The risk mapping in dry land and rainfed land shows that the highest risk source come from pests. In general, dry land farmers and rainfed land farmers have similar strategies, i.e: doing replanting and spraying pesticides for controlling pests. Key words: corn farming, income, risk, risk mapping